The effect of a large expansion of pre-primary school facilities on preschool attendance and material employment - Samuel Berlinski; Sebastian Galiani (Institute for Fiscal Studies (IFS), 2004)
We provide evidence on the impact of a large construction of pre-primary school facilities in Argentina. We estimate the causal impact of the program on pre-primary school attendance and maternal labor supply. Identification relies on a differences-in-differences strategy where we combine differences across regions in the number of facilities built with differences in exposure across cohorts induced by the timing of the program. We find a sizeable impact of the program on pre-primary school participation among children aged between 3 and 5. In fact, we cannot reject the null hypothesis of a full take-up of newly constructed places. In addition, we find that the childcare subsidy induced by the program increases maternal employment and that this effect is in line with the one previously found for the US.
Keywords: I28; J13; O15; 330; Kinderbetreuung; Wirkungsanalyse; Bildungsertrag; Weibliche Arbeitskräfte; Argentinien